PENGEMBANGAN MODUL BERBASIS REALISTIK UNTUK MATERI PECAHAN PADA PEMBELAJARAN MATEMATIKA KELAS V MIN KORONG GADANG KECAMATAN KURANJI - êAzizah, Nur; Rahmi, Rahmi; Harisman, Yulyanti (STKIP PGRI Sumbar, 2014)
ABSTRACT The research and development were motivated of intructional materials used in teaching proces, it is not accordance with the characteristics of the students. Textbooks used by student do not understand and facilitate the student to perform self-regulated learning. Solution offered to this problem is the development of realistic based modules for material fractions. This development aims to determine the validity of the module realistic basic for material fractions. This study used model of 4-D which consisted of 4 phases: definition, design, development and disseminate. The stages through which this reasearch is only the third stage of development. Stage development had validated. Module 3 validated by validators of mathematics and Indonesian. Descriptive data were analyzed with validation results are very valid in terms of content and construck. This means Module Based on Realistic Mathematics Learning Material On Class V MIN Korong Gadang has valid to be used as teaching materials.